XRF- Analysis of silver objects from Olympia - Grethe, Rebecca-Sophie (Πανεπιστήμιο Πελοποννήσου, 2019)
For this study, XRF analyses were performed on silver objects and silver decorations of helmets from the archaeological site of Olympia (Greece) to find possible correlations between their metal composition and the period of their manufacture. The analysed finds date from the archaic to the Byzantine period, with a focus on the archaic period. Quantitative results were gathered for 24 finds, including silver decoration of 6 helmets dating to the archaic period. The obtained results show a correlation between the silver content and the period of manufacture, as well as an increasing percentage of minor chemical elements with time. Differences between the elemental compositions of decorations of three helmets and the archaic objects, respectively, were observed. A measurable amount of zinc in some helmet decorations raises the question if it derives from the incomplete smelting of the ore or from the alloying material. The objects from Roman and Byzantine times contain zinc that certainly derives from brass added to the silver. The bismuth/lead ratio and gold content allow an insight to a discrimination of ore sources between the analysed finds, leading to an estimation of 6-8 different sources for the objects found in Olympia. The observed lead and bismuth values are helpful for the understanding of the process and ore type used to produce the silver. Although a positive identification of provenance was not possible but would require complementary analysis, some ore sources could be excluded.
Keywords: Φασματοσκοπία Φθορισμού ακτίνων Χ στην αρχαιολογία; Ασήμι -- Ανάλυση; Αργυροχοΐα, Αρχαία -- Ελλάδα -- Ολυμπία; Αργυροχοΐα -- Ελλάδα -- Ολυμπία; Ολυμπία (Ελλάδα) – Αρχαιότητες; Φασματοσκοπία Φθορισμού ακτίνων Χ; Αρχαιολογία; Ασήμι; Ανάλυση; Αργυροχοΐα; Ολυμπία